KONSEP KEINDAHAN DALAM Al QURAN - Agus Syihabudin (Jurnal Sosioteknologi, 2010)
As a kalam Allah revealed to the last prophet of all time, not only the Koran is sacred from the lack and error, but also hopstik and aesthetic. The contents of the Qur'an contains the stories that give a very high wisdom score, a comprehensive history of the various sides of human life, an amazing gesture nature and the latest proven technology, and the universal values of human life. To transfer the values, God choses an energetic media and aesthetic, that is the language with asalib al kalimat (said the force) is very dynamic. Dynamics of expression of style that makes each language has a depth Quran meaning that seems endless. One of the beautiful language of the Quran is iltifat, which recalled the style change from the patterns of dialogical patterns informative or otherwise. According to the students of knowledge of the Quran ( 'Ulum al Quran), the language changes or iltifat ussually occur through six patterns, ie patterns of change in the form of words, word numbers, pronouns, vocabulary, tools, and patterns of change of the verb to a noun or vice versa. Iltifat is one of the concepts of language beauty that the Quran comes from the owner of all beauty.